Pengaruh Model Kooperatif Tipe Snowball Throwing terhadap Kemampuan Pemahaman Konsep Matematika ditinjau dari Pengetahuan Awal Peserta Didik - Aziz, Nurjannah; Rasyid, Muhammad Rusydi; Baharuddin; Nur, Fitriani; Nur Miftahul Jannah (Faculty of Tarbiyah and Teacher Training, 2023)
This study aims to determine the effect of the Snowball throwing (ST) cooperative learning model in terms of students' prior knowledge on the ability to understand mathematical concepts for class VII SMP Negeri 13 Makassar. The method used was quantitative with a quasi-experimental research type and a 3 x 2 factorial design. The population in this study were all class VII students of SMP Negeri 13 Makassar totaling 363 people. The sample in this study was class VII 10 as the control class while class VII 4 as the experimental class. The data analysis technique used is descriptive statistical analysis and inferential statistical analysis. Based on the results of data analysis using SPSS version 20, the value of F = 0.606 and the value of Sig. = 0.548 > 0.05 so that H0 is accepted. Therefore, it can be concluded that there is no influence of the snowball throwing cooperative model in terms of students' prior knowledge of the ability to understand mathematical concepts for class VII SMP Negeri 13 Makassar.